2011
DOI: 10.1029/2011jf001976
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and testing of upland hillslope evolution models in a dated landscape: Banco Bonito, New Mexico

Abstract: [1] In this study we tested upland hillslope evolution models and constrained the rates of regolith production, colluvial transport, and eolian deposition over geologic time scales in a dated volcanic landscape in northern New Mexico using field measurements of regolith thickness; geochemical analyses of regolith, bedrock, and regional dust; numerical modeling of regolith production and transport; and quantitative analyses of airborne light detection and ranging (lidar) digital elevation models (DEMs). Within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 56 publications
(113 reference statements)
2
43
0
2
Order By: Relevance
“…An alternative approach is to assume that the flux is proportional to the soil thickness measured normal to the tangent of the slope for relatively thin soils (i.e., less than ~1 m): q=κnormaldhcosθz1()||ztrue/Sc2where κ d has units of length 1 time −1 [ Furbish et al ., ; Roering , ]. In this paper, we adopt equation () to model the colluvial sediment flux based on the fact that depth‐dependent transport has been shown to lead to more accurate predictions of soil thickness in well‐constrained field cases [e.g., Heimsath et al ., ; Pelletier et al ., ]. The coupling between soil thickness and colluvial sediment transport is included via the h dependence on the right side of equation ().…”
Section: Numerical Modelingmentioning
confidence: 81%
“…An alternative approach is to assume that the flux is proportional to the soil thickness measured normal to the tangent of the slope for relatively thin soils (i.e., less than ~1 m): q=κnormaldhcosθz1()||ztrue/Sc2where κ d has units of length 1 time −1 [ Furbish et al ., ; Roering , ]. In this paper, we adopt equation () to model the colluvial sediment flux based on the fact that depth‐dependent transport has been shown to lead to more accurate predictions of soil thickness in well‐constrained field cases [e.g., Heimsath et al ., ; Pelletier et al ., ]. The coupling between soil thickness and colluvial sediment transport is included via the h dependence on the right side of equation ().…”
Section: Numerical Modelingmentioning
confidence: 81%
“…Properties of the canopy elevation structure such as the mean and standard deviation of the height of canopy returns ( V mean and V sd , respectively) can be readily extracted from LiDAR [e.g., Nilsson , ; Naesset , ; Lefsky et al ., ; Holmgren et al ., ; Donoghue and Watt , ] and may provide useful indicators of AGB [e.g., Hall et al ., ; Clark et al . ; Pelletier et al ., ; Saatchi et al ., ]. Clark et al .…”
Section: Methodsmentioning
confidence: 99%
“…Pelletier et al . [] used a 1 m resolution canopy height map derived from LiDAR to demonstrate a negative relationship between mean C HT and V mean , suggesting that vegetation cover may be controlling the sediment transport coefficient D .…”
Section: Methodsmentioning
confidence: 99%
“…Roering (2008) and Hurst et al (2012) demonstrated that hilltop curvature scales with erosion rate and as such demonstrated the importance of accurately constraining the impact of grid resolution on this landscape parameter. Its importance is highlighted by an increasing number of studies using this relationship as a proxy for erosion rate (Pelletier et al, 2011;Hurst et al, 2013c, b;Grieve et al, 2016b). Hilltop curvature can also be used to constrain the sediment transport coefficient of a landscape where an independent constraint on erosion rate is available (Hurst et al, 2013c).…”
Section: Measuring Curvature From Topographymentioning
confidence: 99%
“…Roering et al (2007) and Hurst et al (2012) demonstrated that the curvature of ridgelines measured from high-resolution topography can be used as a proxy for erosion rates in soil-mantled landscapes. This observation has been used in many studies in which cosmogenic radionuclide-derived erosion rates are unavailable (Pelletier et al, 2011;Hurst et al, 2013c, b;Grieve et al, 2016b). However, it can also be used in locations with an independent constraint on erosion rates in order to quantify a sediment transport coefficient that relates hillslope sediment flux to the topographic gradient, which is set by the material properties of soils (Furbish et al, 2009).…”
Section: Introductionmentioning
confidence: 99%